The Histomorphometry of The Small Intestine on Turkey (Meleagris Gallopavo) at Different Age Levels - Dian Masyitha; Nurul Armita; Muslim Akmal; Zainuddin Zainuddin; Erdiansyah Rahmi; M. Jalaluddin; M. Nur Salim; Mustafa Sabri; Cut Dahlia Iskandar; Baidillah Zulkifli (The Faculty of Veterinary Medicine of Syiah Kuala University, 2023)
This study aims to determine the histomorphometry of the small intestine of turkeys (Meleagris gallopavo) at different age levels. This study used a completely randomized design. This study used 18 male turkeys, divided into 3 groups of ages 8, 16, and 24 weeks, each group comprising 6 turkeys. The necropsied turkey's small intestine was taken into histological preparations and stained with haematoxylin-eosin (HE). The results showed that the histological picture of the small intestine layer of turkeys at different age levels consisted of four layers: tunica mucosa, tunica submucosa, tunica muscular, and tunica serosa. Histomorphometrically, there was an increase in the thickness of all layers of the small intestine from 8 and 16 weeks of age (P0.05), and the height of the intestinal villi increased in all parts of the small intestine at 8, 16 and 24 weeks of age (P0.05 ). In conclusion, with histomorphometric measurements, it can be seen that there are differences in the three age groups.